Terorisme Kontemporer Dunia Islam - Sokhi Huda (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This study is inspired by the problem of claims against terrorism as an expression of momentary interest, activities program, and products of history constructivism. To solve such problem, the study uses a critical historical analysis approach of Karl Rudolf Bultmann. The study concludes that terrorism, as a part of the wholeness of history, has played critical roles, namely the control role to the tyrannical-dominance and the role of ideology actualization. With the provision of institutionalized historical legacy, terrorism is not merely a temporary expression but it penetrates into borders of period of the history. In addition, with an emphasis on problem solving at the contemporary era, terrorism action is charged to provide a momentary response. Conceptual sources of this study are the view of Ahmad Jainuri about the character of terrorism and the view of Diniesh D’Souza on the profile and the main motive of terrorism. Based on evidences, data, and discussions of experts as well the terror doers themselves, the author argues that the essential meaning of terror—as a compelled action—lays in the fact that it is a noble meaning of historical and ideological aspects as well as a transcendent honor, which cross over the boundary of all conditions or all kinds of worldly reward. Keywords: Terrorism, contemporary, Islam, action.